Projectile Failure Mechanisms on The Ballistic Multilayer and Ceramic Laminated Composite Panels - Satoto, Rahmat (Teknologi Indonesia, 2015)
Impact on composite structures was a critical topic with great importance in the ballistic materials. Laminated composites have great potential in the design of lightweight armour. This paper presents an experimental study of the ballistic behavior of full metal jacketed projectiles on multilayer kevlar composites and ceramic-laminated kevlar panels. Both kind the ballistic panels were serial shot tested with 9 mm caliber bullet. The projectile velocity was 436 15 m/s and weight of 8.2 g (124 grain). Local as well as global deformations during impact was considered in the evaluation of indentation, penetration, perforation and delamination phases. The delamination was increased with serial number of shots. It was found that a composite panel with areal density of 16.4 kg/m2 and thickness of 10.5 mm comply with level IIIA of NIJ 0101.04 Rev.A. Understanding crack propagation and damage development under high energy impact loads may open new opportunities for the use of these composites in lightweight armour applications.